Coia a normas internacionales de contabilidad de las cuentas de instrumentos financieros en la empresa Materiales EMO S.A.S (2013)
the International Accounting Standards are a useful tool for companies, governments and investors that want to consolidate the financial information that has been issued by all the companies which are involved in the global economy. Our country has adopted International Accounting Standards through 1314 law from 2009; law that regulates the Principles and standards about Accounting and financial information accepted in Colombia. EMO MATERIALES COMPANY S.A.S is one of the first institutions that must adopt this law. That taking into account the number of workers the company has (more than 200 employers) and taking also into account the imports the company makes; which represent more than 50% of the total purchases these requirements were given by the superintendence of societies trough external circular 01-003795 from January 2013.